Technology Readiness and Acceptance as Predictors of Bim Adoption Intention: A Tram Study an a Project Management Consultancy - Harrie Awan Setya Pamunkkaz; Tri Joko Wahyu Adi (Newinera Publisher, 2026)
Building Information Modeling (BIM) is a critical digital innovation for improving coordination and decision-making in construction project management; however, its adoption among project management consultancies in Indonesia remains limited. This study examines how technology readiness and technology acceptance influence BIM adoption intention in a pre-adoption consultancy context using the Technology Readiness and Acceptance Model (TRAM). A confirmatory survey was conducted at a state-owned project management consultancy involving 85 respondents from management and project site teams. Data were analyzed using the Relative Importance Index (RII) and Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that BIM adoption intention is mainly driven by perceived usefulness (β = 0.531, p < 0.001), followed by perceived ease of use (β = 0.263, p = 0.037). The TRAM model explains 55.7% of the variance in adoption intention (R² = 0.557). Innovativeness plays an important enabling role by positively influencing perceived usefulness (β = 0.387, p = 0.002) and perceived ease of use (β = 0.481, p = 0.001), while optimism and insecurity do not show significant effects. Descriptive analysis further indicates that BIM is highly valued for its long-term organizational benefits (RII = 0.925) and early problem detection capability (RII = 0.915). No significant perceptual differences are found between management and project site teams. These findings suggest that BIM adoption intention in project management consultancies is primarily shaped by performance-related and usability perceptions, underscoring the importance of targeted training, infrastructure readiness, and organizational support to translate intention into effective implementation.